2004
DOI: 10.1142/s0217751x04018361
|View full text |Cite
|
Sign up to set email alerts
|

Gauge Transformations, BRST Cohomology and Wigner's Little Group

Abstract: Abstract:We discuss the (dual-)gauge transformations and BRST cohomology for the two (1 + 1)-dimensional (2D) free Abelian one-form and four (3 + 1)-dimensional (4D) free Abelian 2-form gauge theories by exploiting the (co-)BRST symmetries (and their corresponding generators) for the Lagrangian densities of these theories. For the 4D free 2-form gauge theory, we show that the changes on the antisymmetric polarization tensor e µν (k) due to (i) the (dual-)gauge transformations corresponding to the internal symm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…The emergence of such kinds of fields is nothing new. This kind of kinetic term turned up, very naturally, in the context of 4D Abelian 2-form gauge theory [15][16][17][18] when the latter was proven to provide a model for the Hodge theory. Obviously, such kind of particles have not yet been detected by the experiments in high energy physics.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of such kinds of fields is nothing new. This kind of kinetic term turned up, very naturally, in the context of 4D Abelian 2-form gauge theory [15][16][17][18] when the latter was proven to provide a model for the Hodge theory. Obviously, such kind of particles have not yet been detected by the experiments in high energy physics.…”
Section: Discussionmentioning
confidence: 99%
“…Its quasi-topological nature has been discussed in [39] and it has been shown that this theory provides a tractable field theoretical model for the Hodge theory in 4D [38,39]. The "extended" BRST cohomology for this theory has been discussed in [40] where the insights from the Wigner's little group play a very crucial role. It would be interesting endeavour to capture the (anti-)BRST and (anti-)co-BRST symmetries for the above 2-form Abelian gauge theory in the framework of superfield formalism and provide geometrical origin for the nilpotent charges in the theory.…”
Section: Discussionmentioning
confidence: 99%
“…It is to be remarked that the absolute anticommutativity of the (anti-) BRST symmetry transformations imply that only one of them would be really the analogue of the exterior derivative (see, equations (28), (69) below). In a similar fashion, it can be seen that the following off-shell nilpotent (s 2 a(d) = 0) and absolutely anticommuting (s d s ad +s ad s d = 0) (anti-) co-BRST symmetry transformations (s (a)d )…”
Section: Absolutely Anticommuting (Anti-) Brst and (Anti-) Co-brst Symentioning
confidence: 99%